Vision of Nikolograd. The endgame - Bagina, Elena (project baikal, 2024)
On June 17, 2024, a defense of a group of students from the Department of Architecture of Residential Buildings, the workshop of Professor M. A. Belov and Associate Professor P. K. Zavadovsky, who took part in a unique experiment, was successfully held at the Moscow Architectural Institute. It took three years to develop a general project for the city of Nikolograd – Klausburg, in which the authors could realize both general and individual plans. The images of Nikolograd architecture have deep historical roots. An attempt was made in student projects to develop the neoclassical and symbolic direction in architecture.